TROUBLE TICKET SYSTEM BERBASIS WEB DAN ANDROID DI PT. Len Industri (Persero) Bandung - , ULFA NOOR AISYAH, Nur Rohman Rosyid,S.T.,M.T.,D.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT. Len Industri is well known as Len, is an electronic and infrastructure industrial corporation. Len focus on the transportation, information and technology, defence, and renewable energy. Internet technology is the main pilar for running the whole corporation activities. Working with dependency of the internet technology has potential risks of the system failure. It can be caused of the Internet connectivity failure, software failure due to the computer virus, cabling problems, and so on. Failure for managing problems will trigger a snow ball trouble that decreases corporation productivity. Due to many kind of failures facing the corporation, Thus, it needs an application that capable for managing all troubles happen in the corporation. This work has proposed an application for managing all trouble in the corporation, named Trouble Ticket Application. It has two sides, first one is a server side based on web, and the second one is client side based on Android. Both sides communicates through the Internet or intranet. The application have significant contributions for the Len company, compare with the conventional procedure to handle the problems. It shorten the procedure of handling the problems, yielding the efficient and optimal troubleshooting happen in the Len company.